Earthquake Geotechnical Engineering 4th International Conference on Earthquake Geotechnical Engineering-Invited Lectures - Pitilakis, Kyriazis D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The book contains the invited keynote and theme lectures presented at the 4th International Conference on Geotechnical Earthquake Engineering (4ICEGE). The conference was held in Thessaloniki, Greece, from 25 to 28 June, 2007, and was organized by the Technical Committee of Earthquake Geotechnical Engineering (TC4) of the International Society of Soil Mechanics and Geotechnical Engineering (ISSMGE), the Hellenic Scientific Society of Soil Mechanics and Geotechnical Engineering and the Laboratory of Soil Dynamics and Geotechnical Earthquake Engineering of Aristotle University of Thessaloniki. It provides a comprehensive overview of the progress achieved to date in soil dynamics and geotechnical earthquake engineering, as well as in engineering seismology and seismic risk assessment and management. In situ and laboratory testing, theoretical issues and numerical modeling of soil dynamics, seismic hazard with emphasis on the long-period ground motion displacements, site effects and microzonation, liquefaction assessment and mitigation, soil-structure interaction, performance based design of geotechnical structures, earthquake resistant design and performance of shallow and deep foundations, retaining structures, embankments and dams, underground structures and lifelines, are all among the different topics covered in this book. Interdisciplinary subjects such as vulnerability assessment of, transportation networks and lifelines as well as of geotechnical structures are also discussed. Finally, the book provides a thorough presentation of the existing worldwide important large-scale testing facilities and geotechnical strong ground motion arrays. The book is organized in nineteen chapters written by distinguished experts and includes the 2nd Ishihara Lecture given by Prof. Izzat M. Idriss in honor of Prof. Kenji Ishihara. The aim is to present the current state of knowledge and engineering practice, addressing recent and ongoing developments while also projecting innovative ideas for future research and development. Audience Earthquake geotechnical and structural engineers, civil engineers, geologists, geophysicists and seismologists will find in this book the most recent advances in soil dynamics, earthquake and geotechnical engineering, as well as their interfaces with geology, geophysics and engineering seismology. It is of interest not only to scientists, engineers and students, but also to those interested in earthquake hazard assessment and mitigation.
SPT- and CPT-Based Relationships for The Residual Shear Strength of Liquefied Soils -- Long Period Strong Ground Motion and Its Use as Input to Displacement Based Design -- Site Effects: From Observation and Modelling to Accounting for Them in Building Codes -- Source and Site Factors in Microzonation -- A Review of Large-Scale Testing Facilities in Geotechnical Earthquake Engineering -- Modelling of Dynamic Soil Problems -- Field Seismic Testing in Geotechnical Earthquake Engineering -- Liquefaction Strengths of Poorly-Graded and Well-Graded Granular Soils Investigated By Lab Tests -- Shallow and Deep Foundations under Fault Rupture Or Strong Seismic Shaking -- Seismic Design and Performance of Surface Foundations -- Liquefaction Performance of Shallow Foundations in Presence of a Soil Crust -- Seismic Design of Pile Foundations for Liquefaction Effects -- Seismic Analysis and Design of Geotechnical Structures -- Simplified Seismic Slope Displacement Procedures -- Developments of Soil Improvement Technologies for Mitigation of Liquefaction Risk -- Remediation Methods Against Liquefaction which can be Applied to Existing Structures -- Lifeline Performance under Extreme Loading During Earthquakes -- Seismic Risk Assessment of Underground Structures under Transient Ground Deformations -- Issues in Seismic Risk Assessment of Transportation Networks.
Keywords: Engineering; Geotechnical engineering; Computational intelligence; Civil engineering; Buildings -- Design and construction; Building; Construction; Engineering, Architectural; Engineering geology; Engineering -- Geology; Foundations; Hydraulics; Soil science; Soil conservation; Engineering; Building Construction; Geotechnical Engineering & Applied Earth Sciences; Civil Engineering; Geoengineering, Foundations, Hydraulics; Soil Science & Conservation; Computational Intelligence; Electronic books